On the modification of the universality of the Hurwitz zeta-function - Laurinčikas, Antanas; Meška, Laimonas (Nonlinear Analysis: Modelling and Control, 2016)
In the paper, the lower limit in the universality inequality for the Hurwitz zeta-function is replaced by an ordinary limit. The cases of continuous and discrete universalities are considered.
Keywords: Hurwitz zeta-function; linear independence; transcendental number; universality